On a Conjecture of Iglehart - Hordijk, Arie; Tijms, Henk (Management Science, 1975)
This paper gives an elementary proof of Iglehart's conjecture about the classical dynamic inventory model. This conjecture states that the minimal total expected cost for a planning horizon of n periods minus n times the minimal long-run average expected cost per period has a finite limit as n → ∞ for each initial stock.